An introduction to global citizenship - Dower, Nigel, 1942- (Edinburgh University Press, 2003)
Nigel Dower's introduction to the idea of global citizenship covers a wide range of issues that will be of great interest to undergraduates studying politics, philosophy, international relations and the social sciences. The book takes into account the consequences of the September events of 2001.